Trends in asylum migration to industrialized countries: 1999 - 2001 - Stephen Castles; Sean Loughma (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
The purpose of this paper is to outline trends and patterns in movements of asylumseekers to Western so-called industrialized countries from 1990-2001. The paper begins by characterizing three distinct phases of asylum migration since the end of the Second World War. It then provides background material on global refugee and asylum movements, using statistics from UNHCR. The data for selected receiving countries and regions is discussed, followed by some remarks on changing routes used by asylumseekers. The selected countries and regions are Australia, Canada, the EU and the USA. Finally, we examine some of the causal factors behind asylum migration and attempt to identify their significance upon flows migration.
Keywords: F22; R23; 330; asylum migration; industrialized countries; root causes; statistical trends